2023
DOI: 10.1177/15248380231178764
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Mental Health Symptom Outcomes in U.S. Veterans and Servicemembers Following Combat Exposure and Military Sexual Trauma

Abstract: Combat exposure (CE) and military sexual trauma (MST) are among the most common types of traumatic experiences faced by veterans and active duty servicemembers and, as such, have both garnered increased research focus over the past decades. However, there has not yet been a critical review of the literature to examine the distinct clinical presentations associated with different trauma types. This is particularly important, as understanding distinct clinical profiles could help researchers and clinicians refin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Although these estimations vary based on the choice of estimation tools and cohort (Hoge et al, 2014), they still reflect a major condition that affects a large part of the veteran population. Moreover, prior research reported that exposure to military trauma was associated with other emotional disorders, such as depression (Yancey et al, 2023), which affects an estimated 9-16% of American veterans (Karstoft et al, 2020;Inoue et al, 2023). Similar rates were reported among veterans of other countries, such as Australia (Carra et al, 2022), Canada (Thompson et al, 2019), and Israel (Shorer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Although these estimations vary based on the choice of estimation tools and cohort (Hoge et al, 2014), they still reflect a major condition that affects a large part of the veteran population. Moreover, prior research reported that exposure to military trauma was associated with other emotional disorders, such as depression (Yancey et al, 2023), which affects an estimated 9-16% of American veterans (Karstoft et al, 2020;Inoue et al, 2023). Similar rates were reported among veterans of other countries, such as Australia (Carra et al, 2022), Canada (Thompson et al, 2019), and Israel (Shorer et al, 2023).…”
Section: Introductionmentioning
confidence: 99%